2009
DOI: 10.1073/pnas.0902725106
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of human aquaporin 4 at 1.8 Å and its mechanism of conductance

Abstract: Aquaporin (AQP) 4 is the predominant water channel in the mammalian brain, abundantly expressed in the blood-brain and braincerebrospinal fluid interfaces of glial cells. Its function in cerebral water balance has implications in neuropathological disorders, including brain edema, stroke, and head injuries. The 1.8-Å crystal structure reveals the molecular basis for the water selectivity of the channel. Unlike the case in the structures of water-selective AQPs AqpZ and AQP1, the asparagines of the 2 Asn-Pro-Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
298
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 305 publications
(310 citation statements)
references
References 51 publications
11
298
0
1
Order By: Relevance
“…The high resolution structures of several AQPs have been resolved (see Tornroth-Horsefield et al, 2010 for review) and these include the structures of human AQP1, 4 and 5 (Murata et al, 2000, Ho et al, 2009, Horsefield et al, 2008. (Harries et al, 2004, Ho et al, 2009, Horsefield et al, 2008, Murata et al, 2000 revealing that the family shares a conserved architecture ( Figure 1).…”
Section: Structure and Function Of Aqpsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high resolution structures of several AQPs have been resolved (see Tornroth-Horsefield et al, 2010 for review) and these include the structures of human AQP1, 4 and 5 (Murata et al, 2000, Ho et al, 2009, Horsefield et al, 2008. (Harries et al, 2004, Ho et al, 2009, Horsefield et al, 2008, Murata et al, 2000 revealing that the family shares a conserved architecture ( Figure 1).…”
Section: Structure and Function Of Aqpsmentioning
confidence: 99%
“…(Harries et al, 2004, Ho et al, 2009, Horsefield et al, 2008, Murata et al, 2000 revealing that the family shares a conserved architecture ( Figure 1). AQPs exist as homotetramers with four AQP subunits per functional AQP tetramer; selective transport of water molecules, glycerol and/or ions occurs through each of the four pores.…”
Section: Structure and Function Of Aqpsmentioning
confidence: 99%
“…There are two isoforms of AQP4 with AQP4-M1 (323 aa) having a 22 amino acids longer N-terminus than AQP4-M23 (301 aa) (14)(15)(16). High-resolution crystal structures of AQP4 showed that the asparagine of each NPA motif forms hydrogen bonds to a water molecule in the center of the channel, which is different from AQP1 where two asparagines from both NPA motifs form hydrogen bonds to one water molecule (17)(18)(19). Some other studies showed different protein folding pathways between AQP4 and AQP1 during biogenesis (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…In orthodox aquaporins, selective water permeability is determined by three specializations (2,(249)(250)(251). First, the narrowest constriction of each monomer, located close to the extracellular entrance, has a diameter of ~2.8 Å, identical to the diameter of a water molecule (252).…”
Section: Aquaporinsmentioning
confidence: 99%
“…To date, however, the mechanism to which these toxins selectively targets dopaminergic cells in the SNpc has been unknown. AQP9 has a particularly broad substance permeability, given its wide and less polar pore compared to orthodox aquaporins (248,250,(256)(257)(258), and a lower pore density towards the hydrophobic face than other aquaglyceroporins, allowing permeation of larger and bulkier substances (250). Permeable substances include the toxin arsenite as well as pyridines, the latter of which structurally resemble MPP+.…”
Section: Selective Vulnerability Mediated By Aqp9mentioning
confidence: 99%